Student perceptions of the community of inquiry framework and satisfaction: Examining the role of academic emotion and self-regulation in a structural model - Xue, Jinyang; Xu, Xiaohui; Wu, Yuhang; Hu, Ping (Frontiers in Education, 2023)
As many schools remain closed during the COVID-19 pandemic, various courses have to be migrated online. Previous studies have showed that students’ satisfaction of the courses could reflect the quality of online learning, which is determined by students’ perception of online courses. Although the community of inquiry (CoI) framework provided an effective tool for measuring students’ perception in online learning, the mechanisms between the CoI and satisfaction, especially the role of academic emotion and self-regulation, still need to be investigated in the online context. The present study aimed to (1) explore the relationships among three elements of the CoI framework; and (2) explore the relationships between the CoI and satisfaction, as well as the mediating role of academic emotion and self-regulation. The data was collected from 461 university students who were taking online courses in China. The results of Structural Equation Modeling showed that teaching presence significantly and positively predicted social presence and cognitive presence; both positive and negative academic emotions played the mediating roles between teaching presence, social presence and satisfaction; self-regulation played the mediating role between teaching presence, cognitive presence and satisfaction. The present study provided empirical evidence for the dynamics among the CoI framework as well as mechanisms between CoI and satisfaction in the online education environment.